Earnings management ethicality and application in the Kenyan Public Sector: A critical review - Robert Odek; Kalundu Kimanzi (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: This is a critical review of the empirical literature on earnings management ethicality and its application in public sector organizations in the Kenyan context. Design/methodology/approach: Semi-systematic review approach and thematic/content analysis technique were utilized in forming opinions on deductions of the study by reviewing previous publications between 2008-2022. Findings: Outcomes of this study portray that the main factors influencing the management of earnings include; a conducive environment that permits practicing creative accounting without stakeholders' knowledge, dodging declaring losses in the economic reports, meeting analyst predictions, circumventing submission of higher taxes, to qualify access to debt, contracting motivations, and to accomplish perks knotted to performance. Moreover, there is legitimate and illegitimate management of earnings since there is no consensus in regard to the ethicality of earnings management. Further, this review evidences that both accrual and real earnings management techniques are practiced by managers during reporting. Additionally, there are mixed results as to whether creative accounting is practiced in the public sector or not, and with reference to Kenya, no studies on earnings management ethicality have ever been conducted. Research limitations/implications: There are limited studies on earnings management ethicality in the public sector both in Kenya and globally. Besides, this is a qualitative study that depended on the previously published data in its entirety. This then, implies that all the findings here are not first-hand and are purely dependent on the findings of other studies that had been published. The researcher, therefore, had no control in regard to ascertaining the accuracy of the previous data analyzed. In mitigating these limitations, the majority of the publications included in this study were from high ranked journals. The bulk of the literature reviewed was from research work already conducted in other countries. Originality/value: This study contributes to accounting theory as an area of study. It depicts the deductive approach of research which can then be embraced by other graduate accounting students in furthering accounting research. Besides, it contributes to strategy makers like the Kenya Accounting Standards Board in the formulation and implementation of accounting principles. It also forms a basis for further research in the management of earnings and its ethicality among public sector firms. That is, no other study has been done in Kenya and just a few studies have been carried out globally.
Keywords: G32; L25; L30; O34; 330; Earnings Management; Earnings Management Ethicality; Techniques of Earnings management